In vitro fertilization and clinical outcomes with advancing age: contrasts between developed and developing countries, mechanisms of failure, and evidence-based strategies to improve pregnancy and live-birth rates - David Aphkhazava; Levan Gulua; Ketevan Kakashvili; Nodar Sulashvili; Devanshu Ganje; Chanchal Rathod; Tharushi Anargali Silva; Lolita Shengelia; Sajin Suresh; Adilaide Hwenda; Onolaja Olayinka Precious; Vedant Anilkumar Malekar (World Scientific Reports, 2025)
Background: The probability of pregnancy and live birth in IVF declines with age, driven largely by oocyte aneuploidy and diminished ovarian reserve, while access, laboratory quality, and comorbidity patterns amplify disparities between developed and developing settings. Methods: Narrative synthesis of recent population reports (CDC, HFEA, ICMART, WHO) and peer-reviewed studies through 14 October 2025 on age-stratified IVF outcomes, male and female age effects, ovarian reserve testing, embryo aneuploidy, laboratory environment, stimulation strategies, embryo transfer policies, and “add-on” interventions. Results: Live-birth rates per embryo transfer fall steadily after age 35 and sharply after 40 (HFEA 2022; CDC 2022). Age-related oocyte aneuploidy is the principal mechanistic driver (Mikwar et al., 2020; Huang et al., 2024). Male age associates with worse semen quality and higher DNA fragmentation but has smaller effects on ART outcomes than maternal age (Martínez et al., 2021; Xie et al., 2025). Outcomes are additionally shaped by endometriosis/adenomyosis burdens and uterine pathology, and by IVF-lab air quality (Liang et al., 2022; Liao et al., 2025; Sciorio et al., 2021). Disparities between developed and developing countries are driven by affordability, infrastructure, and regulation (WHO, 2024; Ombelet et al., 2019; Njagi et al., 2023). Evidence-based practices that improve success and safety include single-embryo transfer with cumulative-LBR focus, GnRH-antagonist protocols with OHSS-mitigation, selective freeze-all in high-risk patients, PCOS-specific measures (e.g., metformin for long agonist cycles), air-quality control, and precise diagnosis/treatment of uterine disease; many popular “add-ons” lack proven benefit (Cochrane/ESHRE, 2021–2023). PGT-A may help selected older patients with multiple blastocysts but shows limited or no benefit overall (Munné et al., 2019; Yan et al., 2021; ASRM, 2024; HFEA, 2025). Conclusions: Age remains the dominant determinant of IVF success. Maximizing cumulative single-embryo live birth while minimizing multiples, addressing modifiable lab/clinical factors, and curbing unproven add-ons can raise success rates. Expanding access and quality standards in low- and middle-income countries (LMICs) is essential to narrow global gaps